Grounded theory of knowledge process on public ecosystem managers in Seoul - Lee, Jeongseok (The International journal of public sector management, 2019)
Purpose The purpose of this paper is to explore the utility of employing knowledge management (KM) as a framework for understanding how public managers perform ecosystem management. The question of how public managers in Seoul acquire, utilize and share knowledge in managing their ecosystems has been responded to by offering a particular conceptual model. Design/methodology/approach This study applies the grounded theory method to build a conceptual model. The model is generated by applying the concept of knowledge process to an investigation of how the urban ecosystem is publicly managed by civil servants in various offices within the municipality of Seoul, Korea. The case study encompasses the management of the 12 regions of Seoul designated as Eco-scenery Preservation Regions (ESPRs) by the Seoul Metropolitan Government. Findings The knowledge process of public managers in managing the ESPRs can be explained by understanding the conceptual model of “learning-by-doing,” which means public managers cannot count much on their knowledge gained previously through their past experience or education and training. Instead, they learn individually in the process of discharging their duties on a daily basis. Research limitations/implications Although the focus is on the knowledge process of public managers, there is no escaping the fact that managerial activities are not performed in a vacuum. Rather, they take place in a complex policy and government context that is not easily captured as the important variables that influence the knowledge process. Thus, it would be worthwhile to extend this study with group, intra-, and extra-organizational-level analyses. Practical implications Usually different contexts lead to different interpretations on the concept of learning-by-doing. This study supplies such an interpretation that diverse ecosystems in Seoul have been managed by the learning-by-doing of public managers, which is characterized specifically as their reactive response, tinkering and limited personal network. Social implications There has not been a definite consensus on the question of what ecosystem management is. Scientists, policymakers and citizens all have different viewpoints on that question. Nonetheless, this study provides a useful perspective on the issue of how various ecosystems have been managed by public managers, who must be a central entity of ecosystem management particularly under the context of municipality. Originality/value Even though KM has been a popular subject of study in business management rather than public management, KM as a framework of study is promising as a means of understanding and potentially supporting the further development of effective ecosystem management by public managers.